Introducing a model of cardiovascular prevention in Nairobi's slums by integrating a public health and private-sector approach: the SCALE-UP study - Steven van de Vijver; Samuel Oti; Thijs Cohen Tervaert; Catherine Hankins; Catherine Kyobutungi; Gabriela B. Gomez; Lizzy Brewster; Charles Agyemang; Joep Lange (Taylor & Francis Group, 2013)
Introduction: Cardiovascular disease (CVD) is a leading cause of death in sub-Saharan Africa (SSA), with annual deaths expected to increase to 2 million by 2030. Currently, most national health systems in SSA are not adequately prepared for this epidemic. This is especially so in slum settlements where access to formal healthcare and resources is limited. Objective: To develop and introduce a model of cardiovascular prevention in the slums of Nairobi by integrating public health and private sector approaches. Study design: Two non-profit organizations that conduct public health research, Amsterdam Institute for Global Health and Development (AIGHD) and African Population and Health Research Center (APHRC), collaborated with private-sector Boston Consulting Group (BCG) to develop a service delivery package for CVD prevention in slum settings. A theoretic model was designed based on the integration of public and private sector approaches with the focus on costs and feasibility. Results: The final model includes components that aim to improve community awareness, a home-based screening service, patient and provider incentives to seek and deliver treatment specifically for hypertension, and adherence support. The expected outcomes projected by this model could prove potentially cost effective and affordable (1 USD/person/year). The model is currently being implemented in a Nairobi slum and is closely followed by key stakeholders in Kenya including the Ministry of Health, the World Health Organization (WHO), and leading non-governmental organizations (NGOs). Conclusion: Through the collaboration of public health and private sectors, a theoretically cost-effective model was developed for the prevention of CVD and is currently being implemented in the slums of Nairobi. If results are in line with the theoretical projections and first impressions on the ground, scale-up of the service delivery package could be planned in other poor urban areas in Kenya by relevant policymakers and NGOs.